Measurement of 3-acetyl-11-keto-beta-boswellic acid and 11-keto-beta-boswellic acid in Boswellia serrata Supplements Administered to Dogs - Erin Miscioscia; Justin Shmalberg; Karen C. Scott (BMC Veterinary Research, 2019)
Abstract Background Osteoarthritis is a common canine disease frequently treated with nutritional supplements that often lack independent verification of ingredients, active ingredient concentration, efficacy, or safety. Human supplements containing Boswellia serrata extracts (BSE) with high concentrations of active constituents 3-acetyl-11-keto-β-boswellic acid (AKBA) and 11-keto-β-boswellic acid (KBA) are bioavailable, safe, and efficacious in the alleviation of symptoms of naturally occurring osteoarthritis in people. Thus, oral AKBA and/or KBA supplementation could be a promising novel therapy for dogs with osteoarthritis. The primary objective of this study was to determine the concentrations of AKBA and KBA within six human and seven canine market formulations containing BSE administered to dogs, using a derivation of the previously validated high performance liquid chromatography (HPLC) method. The secondary objective was to compare measured concentrations to label claims. Results The mean concentrations of AKBA and KBA within the formulations tested were 42.3 mg/g AF (0.1–155.7 mg/g AF) and 5.2 mg/g AF (0–24.8 mg/g AF), respectively, with four of the formulations containing an undetectable amount of KBA. None of the market formulations had a label claim for KBA. For the five tested formulations with a label claim for AKBA, the mean percentage of detected AKBA was 173% of the concentration listed on the label (range: 114–224%). Formulations claiming to contain AKBA had a mean AKBA concentration of 98.2 mg/g AF, significantly higher than formulations claiming only to contain BSE (7.4 mg/g AF; p = 0.01). Conclusions This study demonstrated a large variation of boswellic acid concentrations in market formulations claiming to contain BSE, with products claiming to contain AKBA containing higher concentrations of AKBA than other products. There was also a large variation in, and overall high, percent difference between label claims and measured concentrations of AKBA. All products met or exceeded label claims. However, differences between label amounts and detected concentrations confirm the need for independent laboratories to quantify concentrations of active ingredients in supplements containing BSE. This would be necessary prior to the use of these formulations in the research or clinical setting.